développer: (3x-5)(-5x+2)+(3x-5)(3x-5) comment faire? (le "x" n'est pas le signe de multiplier mais la lettre x)

CALCULER: (3x-5)(-5x+2)+(3x-5)(3x-5) pour "x" = 1

factoriser: (3x-5)(-5x+2)+(3x-5)(3x-5) (le "x" n'est pas le signe de multiplier mais la lettre x)

2

Réponses

2012-12-15T11:58:19+01:00

(-15x²+6x+25-10)+ (9x²-15x-15x+25)

 

= -15x²+31x -10 + 9x² -30x +25

= -6x² +x +15

 

pour x = 1, l'expression = 6²+1+15 = 36 +1 +15 = 52

 

Factorisation

 

(3x-5)(-5x+2)

2012-12-15T12:05:16+01:00

(-15x²+6x+25x-10)+(9x²-15x-15x+25)

=-15x²+31x-10+9x²-30x+25

=-6x²+x+15

 

Apres tu remplace x par 1

-6x²+x+15

= -6(1)²+1+15

=-6+1+15

=10

 

Factoriser :

(3x-5)[(-5x+2)+(3x-5)]

=(3x-5)(-2x-3)